1949
DOI: 10.1002/cber.19490820115
|View full text |Cite
|
Sign up to set email alerts
|

Über die wachstumshemmenden Eigenschaften von Nitroverbindungen

Abstract: Die durch verschiedene Nitroverbindungen verursachte Wachs‐ tumshemmung wurde an einer Reihe von Bakterien und Pilzen sowie an der Keimung von Kressesamen in vitro untersucht. Einige nitrierte Derivate des Phenyl‐thienyl‐(2)‐sulfids und des Phenyl‐furyl‐(2)‐sulfids wurden dargestellt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

1950
1950
2000
2000

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 23 publications
0
12
0
1
Order By: Relevance
“…In addition, previous authors have concluded from a study of nitrofurans, nitrothiophenes, nitrobenzenes, and related compounds, that ease of reducibility plays a major role in the antibacterial effectiveness of heterocyclic nitro compounds (16). These authors also proposed a relationship between the redox potential developed by the organism in culture and that required by the inhibitory nitrofuran, implying that interference with microbial reproduction was associated with formation of a reduction product (hydroxylamine) from the nitro compound (17). Other workers have measured these reduction potentials and confirmed these proposals (18).…”
Section: Resultsmentioning
confidence: 93%
“…In addition, previous authors have concluded from a study of nitrofurans, nitrothiophenes, nitrobenzenes, and related compounds, that ease of reducibility plays a major role in the antibacterial effectiveness of heterocyclic nitro compounds (16). These authors also proposed a relationship between the redox potential developed by the organism in culture and that required by the inhibitory nitrofuran, implying that interference with microbial reproduction was associated with formation of a reduction product (hydroxylamine) from the nitro compound (17). Other workers have measured these reduction potentials and confirmed these proposals (18).…”
Section: Resultsmentioning
confidence: 93%
“…This is illustrated in Table 7, in which the activities of four pairs of nitro-and aminoimidazoles are compared. Dann & Moller (1947, 1949 had similarly observed that aminothiophenes and aminofurans were inactive. It is probable that the reactive forms of all of these drugs are partially reduced intermediates which are highly unstable ; likely candidates are the hydroxylamino-or nitroso-derivatives (Dann & Moller, 1949;Paul et al, 1960;McCalla et al, 1970).…”
Section: B P Goldstein and Othersmentioning
confidence: 99%
“…Nitroalkenes are considered important because of their biological activities as insecticidal [1,2], fungicidal [2±5], bactericidal [6,7], rodentrepellent [8], and antitumor agents [9] as well as of other pharmacological values [6±9]. They have proved to be suitable precursors for a wide variety of target molecules.…”
Section: Introductionmentioning
confidence: 99%